Ponesimod protects against neuronal death by suppressing the activation of A1 astrocytes in early brain injury after experimental subarachnoid hemorrhage - Zhang, Lifang; Guo, Kecheng; Zhou, Jian; Zhang, Xianhui; Yin, Shigang; Peng, Jianhua; Liao, Yuyan; Jiang, Yong (Journal of neurochemistry, 2021)
As an important initiator and responder of brain inflammation in the central nervous system (CNS), astrocytes transform into two new reactive phenotypes with changed morphology, altered gene expression and secretion profiles, termed detrimental A1 and beneficial A2. Inflammatory events have been shown to occur during the phase of early brain injury (EBI) after subarachnoid hemorrhage (SAH). However, the phenotype transformation of astrocytes as well as its potential contribution to inflammatory status in the EBI of SAH has yet to be determined. In the present study, both in vivo and in vitro models of SAH were established, and the polarization of astrocytes after SAH was analyzed by RNA‐seq, western blotting, and immunofluorescence staining. The effect of astrocytic phenotype transformation on neuroinflammation was examined by real‐time quantitative PCR (RT‐qPCR) and enzyme‐linked immunosorbent assay (ELISA). We demonstrated that astrocytes were transformed into A1 astrocytes and caused neuronal death through the release of pro‐inflammatory factors in EBI after SAH. Importantly, Ponesimod, an S1PR1 specific modulator, exerted neuroprotective effects through the prevention of astrocytic polarization to the A1 phenotype as proved by immunofluorescence, neurological tests, and TUNEL study. We also revealed the role of Ponesimod in modulating astrocytic response was mediated by the signal transducer and activator of transcription 3 (STAT3) signaling. Our study suggested that Ponesimod may be a promising therapeutic target for the treatment of brain injury following SAH. Following SAH, S1PR1 signaling is activated in astrocytes favouring subsequent transformation of astrocytes into the neurotoxic A1 reactive subtype via the phosphorylation of STAT3. Conversely, the S1PR1 specific modulator, Ponesimod, blocks the polarization of A1 astrocytes and their neurotoxic consequences.